Development of Mobile Educational Services Application to Improve Educational Outcomes using Android Technology - El-Sofany, Hosam Farouk; El-Seoud, Samir Abou; Alwadani, Hassan M.; Alwadani, Amer E. (International Journal of Interactive Mobile Technologies (iJIM), 2014)
Mobile devices have become instruments that allow new ways of interacting with institutional services. This paper describes the development of the Mobile Educational Services Application (MES app) for the Android platform. This app allows access to mediated and self-access services, as well as databases, announcements, registration, events, book consultations, schedules, etc. The project provides Mobile and Web-based application tools (apps) that allow online access for different users - students, instructors, and administrators. The app provides students with a user friendly, generic, web-based GUI to request educational services, to send text message inquiries, to add, drop, or defer courses, etc.. The app allows instructors to send or receive text messages to and from students using the mobile or web-based interface of the app. In addition to system monitoring, the app provides administrators an online tool to manage, add, update, and delete system information. This tool seeks to be one of the more useful economic apps that use Android technology for applications, using Tablets and mobile devices, for the use of students, instructors and administrators in accessing services in an educational institution.